DE GARENGEOT HERNIA: AN ATYPICAL PRESENTATION IN AN ELDERLY MALE AND SURGICAL APPROACH - ULLAH , W; MUHAMMAD , F; REHMAN , MU; ATTAULLAH , A; AHMAD , F (Biological and Clinical Sciences Research Journal, 2024)
De Garengeot hernia is a rare condition where the appendix is located within a femoral hernia. Diagnosing it can be difficult, as it is often mistaken for an Amyand's hernia through visual examination and ultrasound, which can be inconclusive. Both types of hernias can cause inflammation, leading to elevated inflammatory markers. Therefore, maintaining a high level of suspicion in suspected cases is crucial to prevent postoperative complications. To ensure an accurate diagnosis, a CT scan of the abdomen and pelvis is recommended.